(untitled) - Hu, Sing-Hwa (Taipei, Taiwan ROC, 2006)
The Sourcebook follows (1) the basic concepts and requirements of GAP to assure food safety in all stages of on-farm and post-production processes; (2) present status and perspectives on GAP and traceability in Asia and Oceania; (3) research and development for environmental impact assessment and risk management; (4) and information technologies to harness GAP and traceability.
Keywords: Sự đổi mới nông nghiệp,Trồng rau,Agricultural innovations,Vegetable processing plants